Paul and the competing mission in Corinth - Goulder, Michael D. (Peabody, MA Hendrickson, 2001)
Includes bibiographical references and indexes.
Keywords: Bible. N.T. Corinthians -- criticism, interpretation, etc; Corinth (Greece) -- church history -- primitive and early church